ANALISIS PENGGUNAAN MODAL KERJA PADA BPR NBP 33 DI ERA PANDEMI COVID 19 - Fathimah, Vidya; Fenny Suryanti (Jurnal Manajemen dan Pemasaran, 2024)
This study aims to analyze the development of working capital usage of Bank Perkreditan Rakyat Nusantara Bona Pasogit 33 (BPR NBP 33) in the Covid 19 pandemic era. In the pandemic era, many companies find it difficult to develop their businesses, so this study wants to see the development of BPR NBP 33 in using working capital efficiently. The data analysis technique used in this study is quantitative descriptive. The data analyzed are in the form of financial reports consisting of balance sheets and reports of sources and uses of working capital in 2018 to 2021. The results of this study can be concluded that in the calculation of the capital change report of BPR NBP 33 Batang Kuis from 2018 to 2021, there has been a fluctuating development. And in the calculation of the sources and uses of working capital of BPR NBP 33 Batang Kuis in 2018, working capital has increased, which means that compared to the sources of working capital, the use of working capital is smaller because in 2018 there was no Covid-19, besides that there was also an increase in accounts in current assets and current liabilities. In the calculation of sources and use of working capital of BPR NBP 33 Batang Kuis from 2019 to 2021, working capital experienced a significant decline, meaning that the use of working capital was greater than the source of working capital itself from 2019 to 2021 and there was also a decrease in accounts in current assets and current liabilities, and from 2019 to 2021 it had entered covid-19. Keywords: Use_of_Working_Capital; People's_Credit_Bank; Covid_19